2011
DOI: 10.1080/00036840802400454
|View full text |Cite
|
Sign up to set email alerts
|

Corporate growth and industrial dynamics: evidence from French manufacturing

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(74 citation statements)
references
References 26 publications
4
68
1
1
Order By: Relevance
“…We employ the same data set for which Duschl and Brenner (2013a) have observed a non-Gaussian (almost Laplacian) distribution of regional industry-specific employment growth rates (the data will be described in the next section). This finding can be connected to previous studies which found heavier-than-Gaussian tails in the empirical distributions of firm (sales and employment) growth rates (Stanley et al, 1996;Bottazzi et al, 2011), of industry (value added) growth rates (Castaldi and Sapio, 2008) and of country (aggregate output) growth rates (Fagiolo et al, 2008). Non-Gaussian distributions might in principle result from a stochastic process governed by Gaussian shocks (Brock, 1999).…”
Section: Methodssupporting
confidence: 82%
“…We employ the same data set for which Duschl and Brenner (2013a) have observed a non-Gaussian (almost Laplacian) distribution of regional industry-specific employment growth rates (the data will be described in the next section). This finding can be connected to previous studies which found heavier-than-Gaussian tails in the empirical distributions of firm (sales and employment) growth rates (Stanley et al, 1996;Bottazzi et al, 2011), of industry (value added) growth rates (Castaldi and Sapio, 2008) and of country (aggregate output) growth rates (Fagiolo et al, 2008). Non-Gaussian distributions might in principle result from a stochastic process governed by Gaussian shocks (Brock, 1999).…”
Section: Methodssupporting
confidence: 82%
“…Bottazzi et al, 2009), and is explored in Coad (2007a). We first focus on the Lag-1 results, already providing the bulk of the message which the addition of a second lag will largely confirm (see below).…”
Section: Resultsmentioning
confidence: 99%
“…The normalization, besides keeping comparability with previous work (e.g. Bottazzi et al (2007), Bottazzi et al (2009)), also removes average time trends common to all the firms caused by factors such as inflation and business cycle effects. 8…”
Section: Data and Variablesmentioning
confidence: 98%
“…The Laplacian nature of the shocks has been found to be robust and invariant across countries and also across sectors, even at different level of sectoral aggregation. See Amaral et al (1997); Secchi (2003, 2006); Bottazzi et al (2011).…”
Section: Pooling Over Time and Laplace Growth Shocksmentioning
confidence: 99%